Implementation of Scratch Training to Improve Computational Thinking-Based Algorithm Skills of Students of SMA Negeri 1 Warunggunung - Bagus Setya; Arip Kristiyanto (SWAGATI : Journal of Community Service, 2026)
The rapid development of digital technology requires students to possess 21st-century skills such as critical thinking, creativity, collaboration, and digital literacy. One of the efforts to develop these skills is through the introduction of basic programming (coding), which can enhance computational thinking, logical reasoning, and problem-solving abilities. However, in reality, many high school students still have limited understanding of basic programming concepts. Therefore, this community service program aims to improve students' understanding of basic programming concepts and develop their computational thinking skills through coding training using Scratch. The method used in this activity consists of several stages, including problem identification, needs analysis, training program design, training implementation, and activity evaluation. The training was conducted at SMA Negeri 1 Warunggunung involving teachers and students as participants. The training method applied is learning by doing, which includes material presentation, hands-on practice in creating simple projects using Scratch, and evaluation through pre-test and post-test to measure participants’ improvement in understanding. The expected results of this activity are an increase in students’ understanding of basic programming concepts, improvement in computational thinking skills, and enhancement of 21st-century skills such as creativity, collaboration, and problem-solving. In addition, this activity is expected to contribute to the development of technology-based learning in schools and support the creation of a better digital literacy ecosystem within the school environment.